From sociocultural categories to socially located relations: Using critical theory in social work practice - Keenan, EK (Families in Society-the Journal of Contemporary Human Services, 2004)
This article applies concepts from critical social theories to shift the profession's discourse from the center-margin relations of generalist-multicultural practice to a model of socially located cross-cultural client-worker relationships. Critical theories examine patterns and meanings enacted within and between people in specific social locations at specific points in history that express particular relations of culture, power, and identity. This framework can help social workers listen, explore, conceptualize, and intervene in a more complex and effective manner. The article summarizes key themes in critical theories, redefines how social workers can use knowledge for practice, and concludes with discussion of a case illustration.
Keywords: dept.swk